Tree-level Growth of Four Oak Species in a Bottomland Hardwood Plantation: Implications for Silvicultural Treatments. Issue 3 (12th April 2021) - Hossain, Shaik M; Olson, Matthew G; Bataineh, Mohammad
Abstract: A 41-year-old bottomland hardwood plantation experiment located in southeastern Arkansas was revisited in 2017 to evaluate basal area increment (BAI) of four oak species [cherrybark oak ( Quercus pagoda Raf.), swamp chestnut oak ( Q. michauxii Nutt.), Nuttall oak ( Q. texana Buckl.), and water oak ( Q. nigra L.)] planted in monoculture in relation with species, spacing, thinning, and neighborhood competition. Species had a significant effect on BAI ( P = 0.04), with cherrybark oak and Nuttall oak demonstrating the greatest (21.5 ± 2.5 cm 2 year −1 ) and lowest (12.7 ± 2.9 cm 2 year −1 ) growth rates, respectively, whereas BAI declined significantly with increasing competition ( P = 0.03). However, rates of growth decline with competition did not differ between species ( P > 0.05 for competition × species term), and thinning and spacing treatments had no effect on BAI ( P > 0.05). We recommend that repetitive thinning, rather than a single thinning, would be appropriate to maintain a positive impact on oak growth. Managing stand density would not only provide opportunities for improving timber production, but also would enhance ecological benefits (e.g., wildlife habitat) through diversification of structure within monoculture plantations.